Vaccination against the Epstein-Barr virus - Rühl, J; Leung, CS; Münz, C (Springer Nature, 2020)
Epstein–Barr virus (EBV) was the first human tumor virus being discovered and remains to date the only human pathogen that can transform cells in vitro. 55 years of EBV research have now brought us to the brink of an EBV vaccine. For this purpose, recombinant viral vectors and their heterologous prime-boost vaccinations, EBV-derived virus-like particles and viral envelope glycoprotein formulations are explored and are discussed in this review. Even so, cell-mediated immune control by cytotoxic lymphocytes protects healthy virus carriers from EBV-associated malignancies, antibodies might be able to prevent symptomatic primary infection, the most likely EBV-associated pathology against which EBV vaccines will be initially tested. Thus, the variety of EBV vaccines reflects the sophisticated life cycle of this human tumor virus and only vaccination in humans will finally be able to reveal the efficacy of these candidates. Nevertheless, the recently renewed efforts to develop an EBV vaccine and the long history of safe adoptive T cell transfer to treat EBV-associated malignancies suggest that this oncogenic γ-herpesvirus can be targeted by immunotherapies. Such vaccination should ideally implement the very same immune control that protects healthy EBV carriers.